Low-carbon concrete prepared from slurry waste and design method of mix proportion of low-carbon concrete
By optimizing the solid content of mud and the mix ratio of concrete raw materials, using fly ash in the mud to replace cement, designing the mix ratio of low carbon concrete, the problem of low mud utilization is solved, and resource utilization and low carbon environmental protection are achieved.
Patent Information
- Application Number
- CN202510334643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-08-01
AI Technical Summary
The low utilization rate of mud in the prior art leads to waste of resources and environmental pollution, and fails to effectively utilize the low-carbon potential of mud in concrete production.
By optimizing the solid content of mud and the mix ratio of each concrete raw material, using fly ash in the mud to replace cement, reducing the heat of hydration reaction, increasing viscosity and water retention, designing a low-carbon concrete mix ratio, including the proportions of slurry, cement, fly ash, sand, gravel, liquid admixture and tap water in different solid contents.
The resource utilization of mud has been achieved, the cost of concrete production is reduced, carbon emissions is reduced, the density and performance of concrete is improved, and the requirements are met.
Smart Images

Figure BDA0005321371220000051 
Figure BDA0005321371220000052 
Figure BDA0005321371220000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and particularly relates to a low-carbon concrete prepared from slurry waste and a design method for its mix ratio. Background Art
[0002] A large amount of slurry is generated during the production process of a concrete mixing plant. This slurry mainly comes from equipment cleaning, mixing tank cleaning, and waste slurry during the production process. Since the slurry contains a large amount of fly ash, cement slurry, and other substances, if directly discharged, it will cause serious pollution to water bodies, soil, and air. The traditional treatment methods for slurry are mostly discharging after precipitation or directly discarding, which not only wastes a large amount of reusable resources but also increases the production cost and environmental burden of enterprises.
[0003] With the enhancement of environmental protection awareness and the popularization of the concept of green buildings, the national environmental protection requirements for concrete mixing plants are becoming increasingly strict, requiring enterprises to effectively treat and recycle the slurry. Therefore, how to effectively use the slurry to prepare ordinary concrete and design corresponding mix ratios according to its different solid contents to prepare low-carbon concrete, so as to solve the environmental protection problem and reduce the production cost of concrete, has become an urgent problem to be solved in current research.
[0004] From the perspective of low carbon, if the slurry can be reasonably applied to concrete production, it has many potential advantages. The fly ash in the slurry can partially replace cement to play a gelling role, thus directly reducing the cement consumption and carbon emissions. However, at present, the research on the application of slurry from concrete mixing plants in concrete production is relatively less, especially the systematic research on the influence of slurry with different solid contents on the low-carbon performance of concrete is lacking, and its great potential in reducing the carbon emissions of concrete has not been fully explored. Summary of the Invention
[0005] The purpose of the present invention is to provide a low-carbon concrete prepared from slurry waste.
[0006] The purpose of the present invention also lies in providing the above-mentioned low-carbon concrete prepared from slurry waste and a design method for its mix ratio.
[0007] The present invention optimizes the solid content of the slurry and the mix ratio of each raw material of ordinary concrete to solve the problems of low slurry utilization rate and unstable concrete performance in the prior art. Reasonably utilize the surplus slurry produced by the concrete mixing plant to realize the recycling of resources, reduce the cement usage and production cost in ordinary concrete, and at the same time ensure that the quality of the concrete meets the requirements of engineering use, realize the recyclability of resources, and achieve the goals of green, low-carbon, and environmental protection.
[0008] The above first object of the present invention can be achieved by the following technical solutions: A low-carbon concrete prepared from slurry waste and a design method for its mix ratio, which is made from raw materials with the following mass ratio: slurry with different solid contents 100 - 150, cement 250 - 350, fly ash 30 - 90, sand 800 - 900, crushed stone 950 - 1050, liquid admixture 5 - 10, tap water 120 - 190, and the solid content of the slurry is 40% - 60%.
[0009] The solid content of the slurry is the mass percentage of the dry basis in the slurry.
[0010] The slurry used in the present invention is regarded as a two-phase combination of fly ash and water, and the solid content of the slurry is between 40% and 60%.
[0011] Calculated by mass parts, the low-carbon concrete prepared from the slurry provided by the present invention includes 100 - 150 parts of slurry, preferably 120 - 130 parts; the slurry is regarded as a two-phase combination of fly ash and water; the solid content of the slurry is between 40% and 60%.
[0012] The present invention selects slurry as one of the raw materials for concrete. On the one hand, by utilizing the "pozzolanic effect" of fly ash in the slurry, it can undergo a secondary hydration reaction with the hydration products generated by cement hydration to form C-S-H and C-A-S-H gels, filling the pores inside ordinary concrete and improving the density of ordinary concrete. On the other hand, the slurry has certain viscosity and water retention, which can increase the cohesiveness of the ordinary concrete mixture and prevent it from segregation and bleeding. In addition, the water in the slurry can meet the requirements of the concrete hydration reaction to a certain extent, reducing the additional water consumption. Using slurry in the preparation of concrete realizes the resource recycling of slurry, greatly reduces the discharge of slurry waste, plays a positive role in protecting the ecological environment, and at the same time reduces the comprehensive production cost of concrete.
[0013] Calculated by 100 - 150 parts of the mass of the slurry, the low-carbon concrete prepared based on slurries with different solid contents provided by the present invention includes 250 - 350 parts of cement, preferably 270 - 300 parts.
[0014] Calculated by 100 - 150 parts of the mass of the slurry, the low-carbon concrete prepared based on slurries with different solid contents provided by the present invention includes 30 - 90 parts of fly ash, preferably 50 - 70 parts.
[0015] Calculated by 100 - 150 parts of the mass of the slurry, the low-carbon concrete prepared based on slurries with different solid contents provided by the present invention includes 800 - 900 parts of sand.
[0016] Based on 100 - 150 parts by mass of the slurry, the low - carbon concrete prepared from slurries with different solid contents provided by the present invention includes 950 - 1050 parts of crushed stones.
[0017] Based on 100 - 150 parts by mass of the slurry, the low - carbon concrete prepared from slurries with different solid contents provided by the present invention includes 5 - 10 parts of liquid admixture, preferably 6 - 8 parts.
[0018] Based on 100 - 150 parts by mass of the slurry, the low - carbon concrete prepared from slurries with different solid contents provided by the present invention includes 120 - 190 parts of tap water, preferably 140 - 160 parts.
[0019] The second object of the present invention can be achieved through the following technical solutions: The design method of the mix proportion of the low - carbon concrete prepared from the slurry waste includes the following steps:
[0020] (1) Select the raw materials for preparing the reference ordinary concrete, including cement, fly ash, sand, crushed stones, liquid admixture and tap water;
[0021] (2) Design the mix proportion of each raw material in the reference ordinary concrete, including:
[0022] (2.1) Determine the amount of cement in the reference concrete and the proportion of cement to fly ash, and calculate the amount of fly ash used;
[0023] (2.2) Determine the water - binder ratio and the dosage of liquid admixture of the reference concrete, and calculate the amounts of water and liquid admixture used, where the water - binder ratio is the mass ratio of water to binder materials, and the binder materials include cement and fly ash;
[0024] (2.3) Determine the cement - sand ratio of the reference concrete, and calculate the total amount of sand and stones used, where the cement - sand ratio is the mass ratio of gel materials to sand and stones, and the sand and stones include sand and crushed stones;
[0025] (2.4) Determine the sand ratio of the reference concrete, where the sand ratio is the mass percentage of sand in sand and crushed stones, and calculate the amounts of sand and crushed stones used;
[0026] (3) Measure the solid content of the slurry, use the dry - basis part of the slurry to replace part of the fly ash in the raw materials of the reference ordinary concrete, and use the water in the slurry to replace part of the water in the raw materials of the reference ordinary concrete, and calculate the replacement amounts of the slurry for fly ash and water;
[0027] (4) According to the replacement amounts of the slurry for fly ash and water, replace the amounts of the corresponding raw materials in the mix proportion of the reference ordinary concrete, and determine the mix proportion of each raw material of slurry, cement, fly ash, sand, crushed stones, liquid admixture and tap water in the low - carbon concrete using slurries with different solid contents as raw materials.
[0028] The present invention provides a design method for the mix proportion of low-carbon concrete using slurries with different solid contents as raw materials. First, select the raw materials for preparing the reference ordinary concrete; secondly, design the mix proportion of the reference ordinary concrete; then measure the solid content of the slurry and calculate the replacement amounts of the slurry for fly ash and water; finally, according to the replacement amounts of the slurry for fly ash and water, replace the corresponding components in the reference mix proportion.
[0029] In the above design method for the mix proportion of low-carbon concrete prepared using slurry as the raw material:
[0030] Preferably, in step (2.1), the mass ratio of cement to fly ash is 1:0.3 - 0.4.
[0031] Preferably, in step (2.2), the water-binder ratio is 0.5 - 0.6:1, and the dosage of the liquid admixture is 1.5% - 2.5% of the total mass of the binder materials.
[0032] Preferably, in step (2.3), the mortar-aggregate ratio is 0.15 - 0.25:1.
[0033] Preferably, in step (2.4), the sand ratio is 0.45 - 0.5:1.
[0034] Preferably, in step (3), the drying method or the separation method is used to measure the solid content of the slurry.
[0035] Preferably, in steps (1) - (4), the cement selected is ordinary Portland cement with a strength grade of P.O 42.5; the fly ash is grade II fly ash with a particle size of 15 - 45 μm.
[0036] Preferably, in steps (1) - (4), the sand is dry river sand with a particle size of 0.2 - 2.5 mm, and the apparent density of the river sand is 2.5 - 2.7 g / cm 3 .
[0037] Preferably, in steps (1) - (4), the crushed stone is continuously graded crushed stone with a particle size of 4.5 - 20 mm; the tap water is urban tap water with a pH value of 6.9 - 7.1.
[0038] Preferably, in steps (1) - (4), the liquid admixture is a polycarboxylate water reducer with a mass percentage content of 10% - 20%.
[0039] The present invention has the following advantages:
[0040] (1) The concrete provided by the present invention rationally utilizes the slurry produced in engineering construction and converts it into one of the raw materials of concrete, realizing the recyclable utilization of slurry resources. At the same time, it reduces the production cost of ordinary concrete, achieving the goals of green, low-carbon, and environmental protection, and has good application prospects.
[0041] (2) The present invention realizes the resource utilization of slurry by rationally using slurries with different solid contents, reduces the production cost of ordinary concrete, reduces the discharge of construction waste, and at the same time ensures the performance of concrete. It can be promoted in various engineering productions, accelerating the green transformation of the industry, promoting the resource utilization of slurry, and providing a new guiding idea for the mix design of ordinary concrete. Specific embodiments
[0042] The present invention will be further described below in conjunction with specific embodiments. The following embodiments are only for illustrative purposes and should not be construed as limiting the present invention. Unless otherwise specified, the raw materials and equipment used in the following embodiments are obtained through conventional commercial channels.
[0043] The recommended but not limited method for obtaining the slurry waste of the present invention is as follows:
[0044] Set up special drainage ditches and catch basins in the concrete mixing and forming area of the concrete mixing plant to collect the slurry generated during concrete production, cleaning, and site flushing.
[0045] Remove larger particles such as stones and sand grains in the wastewater with a grille, and further filter out fine suspended solids through a filter screen.
[0046] Dilute the waste slurry with tap water for urban use to make the solid content 40 - 60%, and add acidic agents such as sulfuric acid and hydrochloric acid to make the pH value of the liquid part of the slurry reach 8 - 10.
[0047] The design method of the mix proportion of the low-carbon concrete prepared by using the slurry waste provided by the present invention includes the following steps:
[0048] (1) Select the raw materials for preparing the reference ordinary concrete.
[0049] In the present invention, the raw materials for preparing the reference ordinary concrete include: cement, fly ash, sand, gravel, liquid admixture, and tap water.
[0050] In the present invention, unless otherwise specified, the raw materials used are conventional experimental raw materials well-known to those skilled in the art.
[0051] In the present invention, ordinary Portland cement is selected. It is recommended but not limited to select ordinary Portland cement with a strength grade of P.O42.5, aiming to reduce the heat generated during the hydration reaction. This cement can undergo a secondary hydration reaction with the hydration product calcium hydroxide to generate more gel bodies, thereby filling the pores and improving the density of the concrete.
[0052] In the present invention, fly ash is recommended but not limited to Class II fly ash with a particle size of 15 - 45 μm. The fly ash added in the present invention can play a "ball bearing" role in the concrete mixture, improving the fluidity of the mixture; it can also reduce the alkali content in the concrete, reduce the probability of the reaction between alkali and reactive aggregates, and reduce the risk of damage to the formed concrete members caused by alkali-aggregate reaction, thereby extending the service life of the members.
[0053] In the present invention, sand is recommended but not limited to dry river sand with a particle size range of 0.2 - 2.5 mm and an apparent density of 2.6 - 2.7 g / cm 3 . The fineness modulus of river sand is usually moderate, which can provide a good grading and help reduce the water consumption and admixture dosage of the concrete.
[0054] In the present invention, crushed stone is recommended but not limited to continuously graded crushed stone with a particle size of 4.5 - 20 mm. The crushed stone has a high strength and can significantly improve the compressive strength, flexural strength and durability of the concrete.
[0055] In the present invention, the liquid admixture is recommended but not limited to polycarboxylate water reducer with a mass percentage content of 10% - 20%. The added polycarboxylate water reducer has a water reduction rate, keeping the mixture in good fluidity and reducing the water demand of the concrete mixture.
[0056] In the present invention, tap water is recommended but not limited to urban tap water with a pH value of 6.9 - 7.1.
[0057] (2) Design the reference ordinary concrete mix ratio;
[0058] (2.1) Determine the amount of cement in the reference concrete and the proportion of cement to fly ash, and calculate the amount of fly ash;
[0059] The mass ratio of cement to fly ash is 1:0.3 - 0.4;
[0060] (2.2) Determine the water-binder ratio of the reference concrete and the dosage of the liquid admixture, and calculate the amounts of water and liquid admixture. The water-binder ratio is the mass ratio of water to the binder, and the binder includes cement and fly ash;
[0061]
[0062] In the formula: W / B is the water-cement ratio, with a value of (0.5 - 0.6):1; m B is the dosage (parts) of the cementitious material; m w is the dosage (parts) of water.
[0063] The dosage of the liquid admixture is 1.5% - 2.5% of the total mass of the cementitious material.
[0064] (2.3) Determine the mortar-aggregate ratio of the reference concrete, and calculate the total dosage of sand and gravel. The mortar-aggregate ratio is the mass parts ratio of the cementitious material to sand and gravel; sand and gravel include sand and crushed stone;
[0065]
[0066] In the formula: B / A is the mortar-aggregate ratio, with a value of (0.15 - 0.25):1; m A is the dosage (parts) of sand and gravel.
[0067] (2.4) Determine the sand ratio of the reference concrete. The sand ratio is the mass percentage of sand in sand and crushed stone, and calculate the dosages of sand and crushed stone;
[0068]
[0069] In the formula: S P is the sand ratio, with a value of (0.45 - 0.5):1; m s is the dosage (parts) of sand; m G is the dosage of crushed stone.
[0070] (3) Measure the solid content of the slurry. Use the dry basis part of the slurry to replace part of the fly ash in the raw materials of the reference ordinary concrete, and use the water in the slurry to replace part of the water in the raw materials of the reference ordinary concrete, and calculate the replacement amounts of the slurry for fly ash and water;
[0071] In the present invention, the method for measuring the solid content of the slurry is as follows:
[0072] Regard the slurry as a binary combination of fly ash and water, and measure the solid content in the slurry through two common solid content measurement methods.
[0073] A. Drying method. First, take a standard and representative sample from the slurry. Secondly, accurately weigh the initial mass of the sample (denoted as m1). Then, put the sample into a drying oven or baking oven and dry it to a constant weight at about 105°C. Accurately weigh the mass of the remaining solid after drying (denoted as m2). Finally, the solid content of the slurry (%) = (m2 / m1) × 100%.
[0074] B. Separation method. First, take a standard and representative sample from the slurry. Use a centrifuge, filter or other equipment to separate the solid particles from the liquid. Then, subject the separated solid particles to normal temperature drying to remove moisture. Accurately weigh the mass of the dried solid particles (denoted as m2). Calculate the solid content based on the total mass of the sample (denoted as m1) and the mass of the solid particles (m2). Finally, the slurry solid content (%) = (m2 / m1) × 100%.
[0075] (4) According to the replacement amount of the slurry for fly ash and water, replace the corresponding raw material amounts in the reference ordinary concrete mix ratio, and determine the mix ratios of each raw material, namely slurry, cement, fly ash, sand, gravel, liquid admixture, and tap water in the low-carbon concrete using slurries with different solid contents as raw materials.
[0076] In the present invention, the raw material replacement formula for preparing low-carbon concrete with slurry includes:
[0077] m f2 = m f1 -(x)×m u
[0078] m w2 = m w1 -[1-(x)]×m u
[0079] Wherein,
[0080] In the formula: m u is the mass (parts) of the slurry; x is the solid content (%) of the slurry; m f1 is the mass (parts) of fly ash in the reference ordinary concrete mix ratio; m f2 is the mass (parts) of fly ash in the ordinary concrete mix ratio prepared with the slurry; m w1 is the mass (parts) of water in the reference ordinary concrete mix ratio; m w2 is the mass (parts) of water in the ordinary concrete mix ratio prepared with the slurry.
[0081] Furthermore, the formula of the low-carbon concrete prepared with the slurry as the raw material in the present invention is obtained, and it is made of the following raw materials with the following mass parts ratio: slurries with different solid contents 100 - 150, cement 250 - 300, fly ash 30 - 90, sand 800 - 900, gravel 950 - 1050, liquid admixture 5 - 10, tap water 120 - 190, and the solid content of the slurry is 40 - 60%.
[0082] The preparation method of low-carbon concrete prepared from slurry waste provided by the present invention comprehensively considers the influence of the solid content of the slurry on the mix ratio design, and modifies the benchmark ordinary concrete mix ratio according to the substitution amount of the slurry for fly ash and water, so as to determine the final mix ratio of low-carbon concrete prepared from the slurry. The concrete prepared by this method can efficiently solve the problem of recycling slurry, greatly promote the resource utilization of slurry, and contribute to the sustainable development of resources. It opens up a new way for the treatment and application of slurry. Due to its excellent performance and environmental protection advantages, this method can be widely promoted in various engineering production scenarios, which helps to accelerate the green transformation process of related industries.
[0083] The following is an illustration of the low-carbon concrete formula obtained by the present invention using the above method through specific examples:
[0084] Example 1
[0085] The low-carbon concrete prepared from 40% solid content slurry waste provided in this example is made from the following raw materials in parts by mass: 100 parts of slurry with 40% solid content; 250 parts of ordinary Portland cement with strength grade P.O 42.5; 50 parts of class II fly ash with a particle size of 15 - 45μm; sand with an apparent density of 2.6 - 2.7g / cm 3 , 850 parts of sand with a particle size of 0.2 - 2.5mm; 1000 parts of crushed stone with a particle size of 4.5 - 5mm; 120 parts of tap water; 7 parts of polycarboxylate water reducer with a mass percentage of 15%.
[0086] Preparation method:
[0087] Put the cement and fly ash into a concrete mixer and perform a dry mixing operation for 120 seconds.
[0088] Add the sand and crushed stone to the concrete mixer in sequence and perform a dry mixing operation for 120 seconds to obtain the mixed dry material.
[0089] Pour the water and polycarboxylate water reducer into the mixing bucket and stir with a stirring rod for 120 seconds to obtain the mixed solution.
[0090] Subsequently, slowly add the mixed solution and the slurry to the above mixed dry material, and then stir for 600 seconds to obtain the low-carbon concrete prepared based on the slurry.
[0091] Example 2
[0092] The low-carbon concrete prepared from the slurry waste with a solid content of 50% provided in this embodiment is made from the following raw materials in parts by mass: 100 parts of slurry with a solid content of 50%, 250 parts of ordinary Portland cement with a strength grade of P.O 42.5; 40 parts of Class II fly ash with a particle size of 15 - 45 μm; with an apparent density of 2.6 - 2.7 g / cm 3 850 parts of sand with a particle size of 0.2 - 2.5 mm; 1000 parts of crushed stone with a particle size of 4.5 - 5 mm; 130 parts of tap water; 7 parts of polycarboxylate water reducer with a mass percentage of 15%.
[0093] Preparation method:
[0094] Put the cement and fly ash into a concrete mixer and perform a dry mixing operation for 120 seconds;
[0095] Add the sand and crushed stone to the concrete mixer in sequence and perform a dry mixing operation for 120 seconds to obtain the mixed dry material;
[0096] Pour the water and polycarboxylate water reducer into a stirring bucket and stir with a stirring rod for 120 seconds to obtain the mixed solution;
[0097] Subsequently, slowly add the mixed solution and the slurry to the above-mentioned mixed dry material, and then stir for 600 seconds to obtain the low-carbon concrete prepared based on the slurry.
[0098] Example 3
[0099] The low-carbon concrete prepared from the slurry waste with a solid content of 60% provided in this embodiment is made from the following raw materials in parts by mass: 100 parts of slurry with a solid content of 60%, 250 parts of ordinary Portland cement with a strength grade of P.O 42.5; 30 parts of Class II fly ash with a particle size of 15 - 45 μm; with an apparent density of 2.6 - 2.7 g / cm 3 850 parts of sand with a particle size of 0.2 - 2.5 mm; 1000 parts of crushed stone with a particle size of 4.5 - 5 mm; 140 parts of tap water; 7 parts of polycarboxylate water reducer with a mass percentage of 15%.
[0100] Preparation method:
[0101] Put the cement and fly ash into a concrete mixer and perform a dry mixing operation for 120 seconds;
[0102] Add the sand and crushed stone to the concrete mixer in sequence and perform a dry mixing operation for 120 seconds to obtain the mixed dry material;
[0103] Pour the water and polycarboxylate water reducer into a stirring bucket and stir with a stirring rod for 120 seconds to obtain the mixed solution;
[0104] Subsequently, the mixed solution and the slurry are slowly added to the above-mentioned mixed dry materials, and then stirred for 600 seconds to obtain low-carbon concrete prepared based on the slurry.
[0105] Comparative Example 1
[0106] The ordinary concrete of this comparative example is made of raw materials with the following mass ratio: 350 parts of ordinary Portland cement with a strength grade of P.O 42.5; 60 parts of Class II fly ash with a particle size of 15 - 45 μm; apparent density of 2.6 - 2.7 g / cm 3 , 850 parts of sand with a particle size of 0.2 - 2.5 mm; 1000 parts of gravel with a particle size of 4.5 - 5 mm; 205 parts of tap water; 8 parts of polycarboxylate water reducer with a mass percentage of 15%.
[0107] Preparation method:
[0108] Put the cement and fly ash into a concrete mixer and perform a dry mixing operation for 120 seconds;
[0109] Add the sand and gravel to the concrete mixer in sequence and perform a dry mixing operation for 120 seconds each to obtain the mixed dry materials;
[0110] Pour the water and polycarboxylate water reducer into the mixing bucket and stir with a stirring rod for 120 seconds to obtain the mixed solution;
[0111] Subsequently, slowly add the mixed solution to the above-mentioned mixed dry materials, and then stir for 600 seconds to obtain ordinary concrete.
[0112] The slump, fluidity, cohesiveness, and bleeding properties of the fresh concrete mortar prepared in Examples 1 - 3 and Comparative Example 1 are shown in Table 1, and the test standard is "Standard Test Method for Properties of Fresh Concrete" (GB / T 50080—2016).
[0113] Table 1 Results of slump, fluidity, cohesiveness, and bleeding properties of fresh concrete mortar prepared in Examples 1 - 3 and Comparative Example 1
[0114] Number Slump / mm Fluidity Cohesion Water retention Example 1 133.6 Good Good No bleeding Example 2 134.7 Good Good No bleeding Example 3 132.8 Good Good No bleeding Comparative Example 1 135.8 Good Good No bleeding
[0115] As can be seen from the results in Table 1, the fresh mortar in Examples 1, 2, 3 and Comparative Example 1 all meet the requirements of "Standard Test Method for Properties of Fresh Concrete" (GB / T 50080—2016) for the slump, fluidity, cohesiveness, and bleeding properties of fresh mortar. ]>
[0116] The test results of the mechanical properties of the concrete prepared in Examples 1 - 3 and Comparative Example 1 under standard curing conditions for 28 days are shown in Table 2, and the test standard is "Standard Test Method for Physical and Mechanical Properties of Concrete" (GB / T 50081 - 2019).
[0117] Table 2 Performance of concrete prepared in Examples 1-3 and Comparative Example 1 at 28 days
[0118] Number Compressive strength / MPa Flexural strength / MPa Example 1 42.11 5.43 Example 2 41.09 5.21 Example 3 41.23 5.13 Comparative Example 1 42.92 5.27
[0119] As can be seen from the results in Table 2, the compressive strength and flexural strength of the specimens in Examples 1, 2, 3 and Comparative Example 1 all meet the standards of concrete C40 in the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019).
[0120] The carbon emissions generated during the production of concrete in Examples 1-3 and Comparative Example 1 are shown in Table 3, and the calculation standard is the "Standard for Calculation of Building Carbon Emissions" (GB / T 51366-2019).
[0121] Table 3 Carbon emissions generated during the production of concrete in Examples 1-3 and Comparative Example 1
[0122] Number <![CDATA[Carbon emissions (kg, CO2) <!-- 7 -->]]> Example 1 217 Example 2 216.1 Example 3 215.2 Comparative Example 1 302.9
[0123] As can be seen from the results in Tables 2 and 3, on the premise of the same flexural strength and compressive strength, the carbon emissions generated during the production of low-carbon concrete with added slurry (such as Examples 1, 2, 3) in the present invention are significantly reduced compared with the production of ordinary concrete without added slurry (Comparative Example 1). At the same time, as the solid content of the slurry increases, the amount of carbon emission reduction gradually increases. Among them, Example 3 reduces the carbon emissions by about 29% compared with Comparative Example 1, which is the most. It shows that the incorporation of slurry can greatly reduce the carbon emissions generated during the production process, and the low-carbon concrete using slurries with different solid contents as raw materials in the present invention meets the requirements of green and low-carbon.
[0124] Example 4
[0125] Different from Example 1, the low-carbon concrete provided in this example, which is prepared from slurry waste with a solid content of 40%, is made from the following raw materials in parts by mass: 120 of slurry with a solid content of 40%, 280 of cement, 60 of fly ash, 900 of sand, 950 of gravel, 8 of liquid admixture, and 130 of tap water.
[0126] Example 5
[0127] Different from Example 1, the low-carbon concrete provided in this example, which is prepared from slurry waste with a solid content of 50%, is made from the following raw materials in parts by mass: 120 of slurry with a solid content of 50%, 280 of cement, 48 of fly ash, 900 of sand, 950 of gravel, 9 of liquid admixture, and 142 of tap water.
[0128] Example 6
[0129] Different from Example 1, the low-carbon concrete prepared with 60% solid content slurry waste in this example is made from the following raw materials in parts by mass: 120 of slurry with 60% solid content, 280 of cement, 36 of fly ash, 900 of sand, 950 of crushed stone, 8 of liquid admixture, and 154 of tap water.
[0130] Example 7
[0131] Different from Example 1, the low-carbon concrete prepared with 40% solid content slurry waste in this example is made from the following raw materials in parts by mass: 150 of slurry with 40% solid content, 300 of cement, 60 of fly ash, 900 of sand, 950 of crushed stone, 10 of liquid admixture, and 160 of tap water.
[0132] Example 8
[0133] Different from Example 1, the low-carbon concrete prepared with 50% solid content slurry waste in this example is made from the following raw materials in parts by mass: 150 of slurry with 50% solid content, 300 of cement, 45 of fly ash, 900 of sand, 950 of crushed stone, 9 of liquid admixture, and 175 of tap water.
[0134] Example 9
[0135] Different from Example 1, the low-carbon concrete prepared with 60% solid content slurry waste in this example is made from the following raw materials in parts by mass: 150 of slurry with 60% solid content, 300 of cement, 30 of fly ash, 900 of sand, 950 of crushed stone, 9 of liquid admixture, and 190 of tap water.
[0136] The method for preparing low-carbon concrete using slurries with different solid contents provided by the present invention comprehensively considers the influence of the solid content of the slurry on the mix design, and makes detailed adjustments and optimizations to the mix design based on the substitution amounts of fly ash and water by the slurry. During the adjustment process, the dosage ratios of various materials are accurately calculated to ensure that the mix design can meet the performance requirements of the concrete while maximizing the utilization of slurry resources under the incorporation of the slurry. On the one hand, it reduces the problems of slurry accumulation and treatment risks, effectively protects the ecological environment, realizes the sustainable utilization of resources, and greatly improves the resource utilization efficiency. On the other hand, it rationally utilizes the advantages brought by the formation of concrete with slurry, transforms this slurry into one of the important components of concrete, and achieves the purpose of improving the density and physical properties of the concrete. This innovative method not only reduces the cost of concrete production to a certain extent but also fully meets the current society's pursuit of green development and sustainable construction.
[0137] The above embodiments are only used to illustrate the present invention, and the protection scope of the present invention is not limited to the above embodiments only. Those of ordinary skill in the art can achieve the purpose of the present invention based on the content disclosed above of the present invention. Any improvements and modifications made on the basis of the concept of the present invention fall within the protection scope of the present invention. The specific protection scope shall be subject to what is recorded in the claims.
Claims
1. A low-carbon concrete prepared from mud waste, characterized in that, It is made from the following raw materials with the following mass ratio: slurry with different solid contents 100 - 150, cement 250 - 300, fly ash 30 - 90, sand 800 - 900, crushed stone 950 - 1050, liquid admixture 5 - 10, tap water 120 - 190, and the solid content of the slurry is 40 - 60%.
2. The design method of the low-carbon concrete mix ratio prepared by using slurry waste according to claim 1, characterized in that, It includes the following steps: (1) Select the raw materials for preparing reference ordinary concrete, including cement, fly ash, sand, crushed stone, liquid admixture and tap water; (2) Design the mix ratio of each raw material in the reference ordinary concrete, including: (2.1) Determine the amount of cement in the reference concrete and the proportion of cement to fly ash, and calculate the amount of fly ash; (2.2) Determine the water - binder ratio and the dosage of liquid admixture in the reference concrete, and calculate the amounts of water and liquid admixture. The water - binder ratio is the mass ratio of water to binder materials, and the binder materials include cement and fly ash; (2.3) Determine the cement - sand ratio of the reference concrete, and calculate the total amount of sand and stone. The cement - sand ratio is the mass ratio of binder materials to sand and stone, and the sand and stone include sand and crushed stone; (2.4) Determine the sand ratio of the reference concrete. The sand ratio is the mass percentage of sand in sand and crushed stone, and calculate the amounts of sand and crushed stone; (3) Measure the solid content of the slurry, use the dry - basis part of the slurry to replace part of the fly ash in the raw materials of the reference ordinary concrete, and use the water in the slurry to replace part of the water in the raw materials of the reference ordinary concrete, and calculate the replacement amounts of the slurry for fly ash and water; (4) According to the replacement amounts of the slurry for fly ash and water, replace the amounts of the corresponding raw materials in the mix ratio of the reference ordinary concrete, and determine the mix ratio of each raw material, namely slurry, cement, fly ash, sand, crushed stone, liquid admixture and tap water, in the low - carbon concrete using slurry with different solid contents as raw materials.
3. The design method according to claim 2, characterized in that, In step (2.1), the mass ratio of cement to fly ash is 1:0.3 - 0.
4.
4. The design method according to claim 2, characterized in that, In step (2.2), the water - binder ratio is 0.50 - 0.6:1, and the dosage of the liquid admixture is 1.5% - 2.5% of the total mass of the binder materials.
5. The design method according to claim 2, characterized in that, In step (2.3), the cement - sand ratio is 0.15 - 0.25:
1.
6. The design method according to claim 2, wherein In step (2.4), the sand ratio is 0.45 - 0.5:
1.
7. The design method according to claim 2, characterized in that In step (3), the drying method or separation method is used to measure the solid content of the slurry.
8. The design method according to claim 2, characterized in that In steps (1) - (4), the cement used is ordinary Portland cement with a strength grade of P.O 42.5; the fly ash is grade II fly ash with a particle size of 15 - 45μm.
9. The design method according to claim 2, characterized in that, The sand described in steps (1)-(4) is dry river sand, the particle size of the river sand is 0.2-2.5 mm, and the apparent density of the river sand is 2.5-2.7 g / cm 3 ; the crushed stone is continuously graded crushed stone, the particle size of the crushed stone is 4.5-20 mm; the tap water is urban tap water, and the pH value is 6.9-7.
1.
10. The design method according to claim 2, wherein In steps (1) - (4), the liquid admixture is polycarboxylate water - reducing agent, and its mass percentage is 10% - 20%.
Citation Information
Patent Citations
Self-compacting concrete prepared from concrete mixing station waste slurry
CN105776994A
Concrete based on industrial waste as raw material and preparation method thereof
CN110482973A
Concrete produced from waste muddy water
CN110922124A
Waste concrete reclaimed sand self-leveling mortar and mix proportion design method thereof
CN119390401A